Factors Affecting Anxiety in College Students Who Are Working on Their Final Project - Masdum Ibrahim; Haerudin Firmansyah; Heni Purnama (STIKep PPNI Jawa Barat, 2023)
Aims: Anxiety is a condition in which a person feels worried, agitated, alarmed, confused, anxious and afraid of things that have not happened. There are various factors that affect anxiety such as internal factors and external factors. Objective: This study aims to find out the factors that affect anxiety in students who are working on their final project. Method: This study used a quantitative descriptive with a Cross sectional study approach and sampling techniques in this study using Total Sampling, a research sample of 117 S1 Nursing students at STIKep PPNI JABAR in Bandung City. Results: The results showed that the average age was 22 years with most respondents being female (81.2%) and who had not conducted a proposal hearing as much as (59.8%). The results of the bivariate analysis showed that there was a relationship between anxiety and a proposal hearing p-value of 0.00 and a correlation value (r) of 9.75 and there was also a relationship between anxiety and family support with a p-value of 0.01 and a correlation value (r) of 12.65. Conclusion: Anxiety can be affected by trial proposals and family support. Suggestion: It is hoped that future research can continue previous research with a larger sample.